Humans as Resources: Commodification of People in Ready, Set, Love (2024) - Valentina Markasović ([sic])
In 2024, Netflix aired its new addition to the already flourishing genre of dystopian TV series. Ready, Set, Love is a Thai comedy romance show set in a world where an epidemic has all but wiped-out men and lowered the birthrate of baby boys to just 1%, turning men into a coveted treasure. Protected at all times, men live in an isolated area called The Farm, and they find partners via the eponymous dating show. The plot intertwines the love story with a gradual exposure of sinister governmental machinations ubiquitous to dystopia. This article aims to analyze how both the game show and the governmental regime objectify and commodify people to gain commercial profit and biopolitical power. The levels of objectification will be examined through the lens of Marxist postulates and reality television scholarship on the one hand and Foucauldian biopolitics on the other.Keywords: biopolitics, commodification, dystopia, Ready, Set, Love, reality television